COPD can mimic the appearance of pneumothorax on thoracic ultrasound. - Slater, A; Goodwin, M; Anderson, K; Gleeson, F (2006)
PURPOSES: To determine the diagnostic accuracy of ultrasound in the diagnosis of pneumothorax in patients with COPD with particular regard to false-positive diagnoses. MATERIALS AND METHODS: This was a single-center, prospective, blinded study. Nine patients with pneumothorax, 9 patients with cystic fibrosis, 17 patients with COPD, and 6 control subjects were studied. Ultrasound clips were recorded at three positions in both hemithoraces of each patient and then reviewed by two observers blinded to patient status. Each clip was scored for the presence or absence of pneumothorax and the degree of observer confidence. RESULTS: The sensitivity and specificity for a pneumothorax were 100% and 84% for the experienced observer and 78% and 81% for the inexperienced observer, respectively. In the COPD patient group, specificity was 71% for the experienced observer and 65% for the inexperienced observer. There were no false-positive diagnoses in the cystic fibrosis or the control group. CONCLUSION: Patients with COPD commonly show signs on ultrasound mimicking a pneumothorax, but this was not seen in patients with cystic fibrosis. In patients with COPD, ultrasound may be used to exclude the presence of a pneumothorax, but it cannot be used to confidently diagnose pneumothorax without using other imaging modalities.